Zooplankton Diversity, Dynamics and Correlation with Physicochemical Parameters at Ugbevwe Pond in Delta State, Nigeria - J.A. Edoreh; T.O.T IMoobe; E. Ikpokpo; M.M. Ubrei-Joe; C.M. Ubrei-Joe (Journal of Applied Sciences and Environmental Management)
Zooplankton are microscopic floating animals, which drift in water and whose swimming power if any, serve mainly to keep them afloat. A field study was conducted to determine the spatial and temporal variation in the zooplankton composition, dynamics and diversity at Ugbevwe Pond, Oghara, Delta State. Zooplankton samples were collected from three stations from August, 2014 to May, 2015 covering the wet and dry seasons. Zooplankton species were sorted and identified using appropriate identification keys. A total of six species of copepod belonging to two subfamilies and a total of five species of Cladocera belonging to three families were encountered. The spatial distribution of species of cladoera shows that of the five species encountered, three species namely Alona eximia, Alona costata and Macrothrix sp. occurred in all three stations. Diaphanosoma sp was restricted to station 1 while Pleuroxus ematus was restricted to station 3. The spatial distribution of species of copepod shows that of the six species encountered, Thermocyclops neglectus, Tropocyclops prasinus, Microcyclops varicans Mesocyclops bodanicola and Eucyclops serrulatus occurred in all three stations while Cryptocyclops bicolor was absent in station 1. Zooplankton was more abundant in the rainy season than the dry season. The relationship between zooplankton and the investigated physicochemical parameters showed that all the zooplankton correlated positively with depth, lead and total  hydrocarbon and negatively with colour, sodium, Calcium, Iron and Zinc.